Thermal Behaviour Assessment of Brick Utilizing Plastic Waste for Enhanced Insulation Properties - Nuranis Yasira, Abd Halim; Fatin Zafirah, Mansur; Noor Intan Shafinas, Muhammad; Mohammad Affendy, Omardin; Nursyafawati, Bakhari (Universiti Teknologi PETRONAS, 2024)
Plastic waste, particularly hazardous types such as high-density polyethylene (HDPE) and Polyethylene terephthalate (PTE), is a critical problem in today’s world. Recycling plastic waste to produce new materials like concrete or mortar is an effective disposal method. One such solution is adding plastic waste to bricks to create an environmentally friendly and cost-effective option to produce high-strength bricks with thermal and sound insulation properties. The study intends to investigate the feasibility of reusing plastic waste as a mixture in brick production as an eco-friendly alternative to traditional bricks. To compare the thermal performance of buildings made of plastic waste bricks and traditional bricks, the researchers digitally created four sample bricks, each containing 0%, 5%, 10%, and 15% HDPE. The thermal performance of the brick-filled plastic bottle walls was then measured on-site at a real-time recording using a chamber and tested with the thermocouples connected to a data logger - T08 software. The results showed that 10% and 15% plastic waste brick composition had higher insulation properties with the difference between internal and external air temperature average of 6°C. The lower the external air temperature with the least amount of plastic waste recorded the lowest temperature difference average of 1°C. At the external temperature of 30°C, the 0% and 5% plastic waste bricks possessed the greater internal temperature, likely due to the external air temperature flow in the box’s confined space. Thus, further research and experimentation are recommended to investigate the thermal conductivity of plastic waste bricks and their correlation with the insulation properties of the material samples.